Clinical characteristics of patients with newly developed acute cholecystitis after admission to the intensive care unit. Issue 3 (May 2019) - Kim, Soo Jung; Lee, Seok Jeong; Lee, Su Hwan; Lee, Jin Hwa; Chang, Jung Hyun; Ryu, Yon Ju
Abstract: Introduction: Critical care patients have many risk factors for acute cholecystitis (AC). However, less data are available regarding newly developed AC in critically ill patients. Objectives: To investigate the clinical features of AC occurring in critically ill patients after admission to an intensive care unit (ICU). Methods: We performed a retrospective cohort study from January 2006 to August 2016 at a tertiary care university hospital. We included patients diagnosed with AC with or without gallstones after ICU admission. All cases of AC were confirmed by gastroenterologists or general surgeons. We excluded patients with AC diagnosed before or at the time of ICU admission. Results: A total of 38 patients were diagnosed with AC after ICU admission between January 2006 and August 2016. Seventeen (44.7%) had acute acalculous cholecystitis, while 21 (55.3%) had acute calculous cholecystitis. The median age was 73 years (interquartile range = 63–81 years), and 22 (57.9%) patients were male. The most common reason for ICU admission was pneumonia or sepsis. The median interval from ICU admission to diagnosis of AC was 11 days (interquartile range = 4.8–22.8 days). Before AC diagnosis, almost 90% of patients used total parenteral nutrition, 68% used opioids, 76% were mechanically ventilated, and 42% received vasoactive drugs. More than half of patients underwent cholecystectomy, and all surgically resected gallbladders had pathology results for cholecystitis. Gangrenous cholecystitis was observed in five patients with acute calculous cholecystitis. The overall mortality was 42.1%, and 1/3 of these deaths were directly associated with AC. The average length of stay in the ICU and hospital was 26.5 and 44.5 days, respectively. Conclusion: The development of AC in the ICU should be carefully monitored, especially in patients who have been infected and admitted to the ICU for more than 10 days. Proper diagnosis and treatment at a critical time could be lifesaving.